Social Entrepreneurship: Implications for Management Practice - Spitzeck, Heiko; Janssen, Frank (Senate Hall, 2010)
Editors' Introduction to the special issue Keywords: Social Entrepreneurship, Entrepreneurship, Corporate Entrepreneurship, Innovation THIS ARTICLE IS FREE OF CHARGE IF PURCHASED WITH ANOTHER ARTICLE FROM THIS ISSUE
Keywords: social entrepreneurship|entrepreneurship|corporate entrepreneurship|innovation